The deposition of thin films of cadmium zinc sulfide Cd1−x Zn x S at 250 °C from spin-coated xanthato complexes: a potential route to window layers for photovoltaic cells - Bakly, Ali A. K.; Spencer, Ben F.; O’Brien, Paul (Journal of materials science, 2018)
Thin films of Cd1−xZnxS (CZS) were prepared by a novel spin coating/melt method from cadmium ethylxanthato [Cd(C2H5OCS2)2] and zinc ethylxanthato [Zn(C2H5OCS2)2] in x ratios of 0–0.15 and of 1. A solution of the precursor(s) in THF was spin coated onto a glass substrate and then heated at 250 °C for 1 h under N2. The thickness of the film formed can be controlled by varying the solution composition and/or the spin rate of the coating. A total metal precursor solution concentration of 50 mM was used in all cases. The films were characterized by p-XRD, SEM, EDX, ICP-AES, XPS, UV–Vis absorption spectroscopy, Raman spectroscopy and resistivity measurements. The band gaps of the films were between 2.35–2.58 and 3.75 eV (0 ≤ x ≤ 0.15 and at x = 1). The resistivity of Cd1−xZnxS films was found to vary linearly with zinc contents, and the properties of the films suggest potential application to photovoltaics as window layers. This work is the first study to demonstrate Cd1−xZnxS thin films by a spin coating/melt method from xanthato precursors.